Konsep Zuhud Pada Ajaran Tasawuf Dalam Kehidupan Santri Pada Pondok Pesantren - Dewi, Ratna (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2021)
This article discussed about the concept of zuhud in the teachings of Sufism in the lives of students at Islamic boarding schools through recitation using the book "Minhajul Abidin and siraj al-Thalibin and Jalalin interpretation". As for instilling the value of zuhud in Islamic boarding school students, namely "takhalli tahalli, and tajalli". Whereas in the application of Sufism values ​​to Islamic boarding school students, namely: getting used to sunnah prayers and fasting sunnah, getting used to wirid activities together, uswatun hasanah, inland Sufism through non-formal and formal education, sincere, honest, qona'ah, hard work, responsibility and tolerance. Keywords: Zuhud Concept in Taswuf Teachings, Santri, Islamic Boarding School Abstrak Artikel ini membahas mengenai konsep zuhud pada ajaran tasawuf dalam kehidupan santri pada pondok pesantren melaui pengajian menggunakan kitab “Minhajul Abidin dan siraj al-Thalibin dan tafsir Jalalin”. Adapun dalam penanaman nilai zuhud pada santri pondok pesantren ialah “takhalli tahalli, dan tajalli”. Sedangkan dalam penerapan nilai tasawuf pada santri pondok pesantren ialah: membiasakan sholat sunnah dan puasa sunnah, membiasakan kegiatan wirid bersama, uswatun hasanah, pedalaman tasawuf melalui pendidikan non formal dan formal, ikhlas, jujur, qona’ah, kerja keras, tanggung jawab dan toleransi. Kata kunci: Konsep Zuhud Pada Ajaran Taswuf, Santri, Pondok Pesantren